Safe to transfuse? An audit on quality and practices in blood transfusion sampling and labelling in the accident and emergency (A&E) department. - John Gyasi Appiah; Lilian Abrafi Yeboah (Clinical Medicine)
Introduction: Blood transfusion sample labelling errors have the potential to cause harm and negatively affect patient experience, because patients may need to undergo repeated venipuncture, which could lead to delays in treatment.1 The British Committee for Standards in Hematology (BCSH) guidelines state that organisations should have a clear policy for rejecting pre-transfusion blood samples that do not meet the minimum labelling requirements and should adopt a ‘zero-tolerance’ approach to sample labelling.2 This retrospective audit aimed to evaluate the quality of transfusion sample collection and labelling practices, assess the reasons for sample rejection in the accident and emergency (A&E) department of Diana, Princess of Wales Hospital in Grimsby, which has a high patient turnover, and suggest specific measures to reduce the incidence of sample labelling errors. Methods: Electronic records of pre-transfusion data for all Blood Transfusion Service (BTS) samples and request forms received from A&E over a 1-month period, from 011 October 2024 to 31 October 2024, were collated. The collated data were analysed to determine the number of rejected BTS samples, the reasons for sample rejection and number of samples that resulted in a blood component transfusion. Data on rejected samples, reasons for sample rejection and total samples leading to a blood transfusion were compiled. Results: During the 1-month period, 287 transfusion samples were collected from A&E and received by the transfusion service laboratory. Of these, 54 samples were rejected, resulting in an 18% rejection rate of all BTS samples. A total of 61 samples led to blood transfusions, with 15 of these samples initially rejected because of sampling or labelling errors (Fig 1). The most common reasons for rejected blood transfusion samples included incorrect patient details on samples and request forms, unnecessary sampling, insufficient or haemolysed samples, and missing information on forms or samples (Fig 2). Conclusion: The high rejection rate can potentially cause patient harm, because rejected samples require repeat sampling, which can raise patient safety concerns, increase turnaround times and lead to negative experiences because of repeated venipuncture and potential treatment delays. The increased rejection rate may be linked to factors such as attitudes toward sample labelling, staff workload and non-adherence to the two-sample rule, which affects the issue of unnecessary sampling. To address this, regular education and continued training sessions for healthcare staff involved in blood transfusion sampling, coupled with individualised feedback on rejected samples, are recommended. These measures aim to improve the accuracy of transfusion sampling and labelling, reduce rejection rates and enhance overall patient safety.